2022
DOI: 10.1136/jcp-2022-208632
|View full text |Cite
|
Sign up to set email alerts
|

UK recommendations for HER2 assessment in breast cancer: an update

Abstract: The last UK breast cancer (BC) human epidermal growth factor receptor 2 (HER2) testing guideline recommendations were published in 2015. Since then, new data and therapeutic strategies have emerged. The American Society of Clinical Oncology (ASCO)/College of American Pathologists (CAP) published a focused update in 2018 that reclassified in situ hybridisation (ISH) Group 2 (immunohistochemistry (IHC) score 2+andHER2/chromosome enumeration probe 17 (CEP17) ratio ≥2.0 andHER2 copy number <4.0 signals/cell), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 79 publications
0
27
0
1
Order By: Relevance
“…The categorisation of five distinct HER2 ISH biological groups from the continuum of HER2 expression in the 2018 ASCO/CAP update highlighted the importance of accurate determination of HER2 status via IHC and ISH testing. Further research is required to evaluate whether these groups benefit from anti‐HER2 therapies to help inform treatment decisions in these patients 13,16–18 . We undertook subgroup analysis to evaluate if particular groups had higher levels of interobserver variability associated with their reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The categorisation of five distinct HER2 ISH biological groups from the continuum of HER2 expression in the 2018 ASCO/CAP update highlighted the importance of accurate determination of HER2 status via IHC and ISH testing. Further research is required to evaluate whether these groups benefit from anti‐HER2 therapies to help inform treatment decisions in these patients 13,16–18 . We undertook subgroup analysis to evaluate if particular groups had higher levels of interobserver variability associated with their reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to evaluate whether these groups benefit from anti-HER2 therapies to help inform treatment decisions in these patients. 13,[16][17][18] We undertook subgroup analysis to evaluate if particular groups had higher levels of interobserver variability associated with their reporting. Low concordance was strikingly evident in group 2 and borderline group 5, as pathologist agreement was not significantly different from the agreement that may occur due to random chance.…”
Section: Manualmentioning
confidence: 99%
“…Current clinical pathways are based on the human interpretation of histopathology slides, and the role of AI algorithms in clinical practice needs to be ascertained. For example, invasive breast cancer is defined as HER2-positive if >10% of tumour cells show strong, complete membrane reactivity [60]. An AI algorithm could potentially distinguish between 8%, 10%, and 12% HER2-positive staining, something the human eye cannot discern.…”
Section: Towards Adoption In the Diagnostic Histopathological Pathmentioning
confidence: 99%
“…ASCO/CAP (2013 version) ( 13 ) suggested that HER2 gene heterogeneity be defined as the presence of individual cell populations with different HER2 copy numbers and/or HER2/CEP17 ratios, accounting for at least 10% of the entire tumor cell population. The 2023 UK guidelines ( 14 ) for HER2 detection stated that at the level of HER2 protein expression, heterogeneity is defined as any cluster of cells (subclones) with strong or moderate expression of intact cell membranes in <10% of tumors; then the IHC score was 2+ and should be tested by in situ hybridization (ISH) ( Figure 1 ). If subclonal cells show weak staining in <10% of tumors that are otherwise regionally negative, the tumor is scored as 1+.…”
Section: Detection Of Heterogeneity Of Her2 Low Expressionmentioning
confidence: 99%